Research on the Adaptability of Development Methods for Offshore Gas Cap Edge Water Reservoirs - Quan, Honghui; Xia, Jinna; Tan, Jie; Guo, Jingmin; Li, Bo (Journal of Theory and Practice in Engineering and Technology, 2025)
The X oilfield has complex reservoir types, including edge bottom water reservoirs and gas cap reservoirs, with complex oil, gas, and water distributions, making it difficult to tap the remaining oil. To optimize the development effect, a typical numerical model of a multilayer gas cap edge water reservoir was established, and the influence of different water body multiples on the degree of recovery was analyzed. The injection production rules for four different area well networks (the reverse nine-point method, the row method, the five-point method, and the triangular well network) were explored. The results show that as the number of water bodies increases, the total degree of recovery of the four well networks decreases, but after the number of water bodies exceeds 10, the degree of recovery decreases to zero. In addition, the gas–oil ratio and remaining oil distribution of different well networks are also affected by water multiples. The reverse nine-point method has the highest recovery rate in the well network, whereas the triangular well network has the lowest, but the final recovery rates of the four well networks are not significantly different.